Последние вопросы и ответы

Найдите значение выражение (a^3+27b^3)*1/3a^2-9ab+27b^1 при условии что a=-3,b=5                                                                                                                                                      упростите выражение x^2-4ax+4a^2/x^2+4ax+4a^2*(x+2a/x-2a)^3

Нет уточнений

Ответы

x^2-4ax+4a^2/x^2+4ax+4a^2*(x+2a/x-2a)^3=(x-2a)^2/(x+2a)^2*(x+2a)^3/(x-2a)^3=(x+2a)/(x-2a)
(a^3+27b^3)*1/3a^2-9ab+27b=(a^2-3ab+9b^2)(a+3b)/3a^2+9b(a-3b)=
=((a-3b)^2+3ab)(a+3b)/3a^2-9b(a-3b)
a-3b=-3-15=-18
a+3b=15-3=12
=(18^2-45)*12/27+45*18=279*4/9+810=124+810=934
Нет уточнений